2005
DOI: 10.1016/j.ejheart.2004.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The significance of CA125 levels in patients with chronic congestive heart failure. Correlation with clinical and echocardiographic parameters

Abstract: Objective: To assess serum levels of carbohydrate antigen 125 (CA125) in patients with chronic congestive heart failure (CHF) and to assess any correlation with clinical symptoms and echocardiographic indices. Patients and methods: We enrolled 77 male patients (mean age: 73F10 years) admitted to the Cardiology Emergency Department (ED) with cardiac symptoms requiring hospitalization. Diagnosis of CHF was based upon medical history or initial echocardiographic evaluation on current admission. Serum CA125 was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 22 publications
(37 reference statements)
8
79
2
2
Order By: Relevance
“…CA-125 was suggested as an emerging marker of poor survival in this group of patients [13]. However, those studies also included those with acute decompositions, which could disable accurate reasoning in the setting of acute congestion, which is known to influence CA-125 level [14]. Besides, RV dilatation and tricuspid regurgitation were not separated from other potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…CA-125 was suggested as an emerging marker of poor survival in this group of patients [13]. However, those studies also included those with acute decompositions, which could disable accurate reasoning in the setting of acute congestion, which is known to influence CA-125 level [14]. Besides, RV dilatation and tricuspid regurgitation were not separated from other potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies found CA 125 levels to be elevated in patients with chronic CHF compared with healthy controls. [17][18][19] Kouris et al 18 demonstrated an association between CA 125 levels and the clinical severity of chronic CHF as well as a weak correlation between CA 125 levels and pulmonary artery pressure. In a recent study, it was .…”
Section: Discussionmentioning
confidence: 99%
“…The prolongation of hospitalization through the use of positive inotropic agents is an expected result, yet prolonged hospitalization in the absence of β-blockers and diuretics could arise from poor clinical conditions or poor prognosis. Recent studies 12,[14][15][16] have shown that CA-125, long useful as a tumor marker, has prognostic importance in many cardiovascular diseases, especially HF. In studies related to HF, CA-125 values correlated with pulmonary artery pressure, pulmonary artery capillary wedge pressure, left atrial volume index, LVEF, brain natriuretic peptide values, New York Heart Association functional class, and pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, in the last decade, a correlation between serum CA-125 levels and cardiopulmonary diseases such as left-and rightsided HF, coronary artery disease, atrial fibrillation (AF), and chronic obstructive pulmonary disease (COPD), has been revealed. [12][13][14][15][16][17][18][19] Although serum CA-125 levels are significantly increased in HF and this increase correlates with the severity of the disease, the relationship between CA-125 and length of stay (LOS) in patients with HF has not yet been evaluated. This study is the first that attempts to evaluate the relationship between the duration of hospitalization and CA-125 levels in patients with HF.…”
mentioning
confidence: 99%